FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN AYAM KAMPUNG DI KABUPATEN MAROS - Hasriani Hasriani; Arifin Arifin; Abd. Asis Pata (Universitas Muslim Maros, 2019)
Demand for meat chicken have tended to the time to time.It is caused by an increase in some people living standard and awareness to mengkomsumsi chicken organic or the flesh of a chicken not through the process engineering.Increase population means increasing chicken meat consumption required.From the farmers the overwhelmed by supply to meet a demand chicken this village has actually faced by farmers who because farmers itself undergoes explained to develop many obstacles and increase livestock numbers chicken in compensate the market. Research aims to understand the factors influencing the chicken in kabupaten maros.The study is done at january - june 2018.Method the sample done with the methods, tracing accedental ) ( that is the consumer the respondents any shopping chicken maros.sampel taken the the research is 30 sampel.data in this research consisting of primary and secondary data. The analysis used is double regression. The result of this research are factors that had have real impact on the price of chicken is the chicken and prices of chicken.